Ferriols on Ferriols and More - Oris, Glenda “Bong” C. (Archīum Ateneo, 2015)
Excerpt: This “interview” consists of excerpts from articles about or by Ferriols. Ferriols’s words are reconstituted as answers to seven questions, seven being, as Ferriols once remarked, “a symbol of completion.” The sources of the quotations are given in footnotes.